LIQUIDITY, SOLVENCY, AND ACTIVITY RATIO IN MEASURING FINANCIAL PERFORMANCE OF CONSTRUCTION COMPANIES LISTED ON THE IDX FOR THE 2019 - 2023 PERIOD (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the effect of liquidity, solvency, and activity ratios on the financial performance of construction companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Liquidity is measured using the current ratio, solvency using the debt to equity ratio, and activity using total asset turnover. Company financial performance is measured through return on assets (ROA). This study uses a quantitative approach with multiple linear regression methods. The data used are secondary data in the form of annual financial reports of construction companies obtained from the official IDX website. Data processing was carried out using SPSS 26 software. The results show that CR has a negative and significant effect on ROA partially, and DER has a negative and significant effect on ROA. Then TATO has a positive and significant effect on ROA. Furthermore, CR, DER, and TATO have a significant effect on ROA simultaneously.